Exploring the Resilience Strategies of Adolescent Men Who Have Sex with Men (MSM) in an Educational City - Faza Kasyiva Az-Zahra; Hengki Tri Hidayatullah; Kheren Carollina Pamintarso; Ijazah Ilmi Rohmah; Dzulkifli Abdullah; Muslihati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The phenomenon of men having sex with men (MSM) in adolescence is becoming a hot topic in almost all levels of society. This is because MSM certainly experiences psychological and sociological burdens. The purpose of this research is to find the configuration of MSM. This research uses a qualitative, phenomenological approach. Data collection was carried out using interview techniques (in-depth interviews) and documentation of 6 key informants and 4 supporting informants who met the criteria. Data were analyzed using MAXQDA software. Data validity testing used triangulation techniques and sources. The findings show that the MSM configuration comprises three phases fundamental, central, and dependency consistent with the theory of MSM identity formation. The fundamental phase is the initial phase; the central phase is the transitional phase; and the third phase is dependency, during which MSM adolescents begin to be active in MSM relationships. In this phase, adolescents experience sociological and psychological burdens. This study addresses the gap in scientific research by exploring the stages that MSM adolescents undergo in forming their identities. By doing so, it enriches the academic literature and serves as a foundation for future researchers in designing appropriate interventions for MSM adolescents. Keywords: resilience, adolescents, MSM